Geochemical Data Supporting a Revised Age Model for Onepoto Maar, Auckland, New Zealand: Insights from Tephra Layers in the Lake Sediment Sequence - Benjamin Laeuchli; Paul C Augustinus; Jenni L Hopkins (PANGAEA, 2025)
We present geochemical data from tephra layers obtained using an Electron Microprobe Analyser (EMPA) contained within the lacustrine sequence that infilled Onepoto Maar lake, Auckland, New Zealand. The dataset includes compositional analyses of 14 rhyolitic, seven basaltic, and two andesitic tephra layers, sourced from the Taupo Volcanic Zone (TVZ), Taranaki Maunga, and the Auckland Volcanic Field (AVF). These data are critical to support the revised age model developed for the Onepoto lake sediment record. Each microprobed tephra layer is characterised by distinctive major and trace element concentrations that facilitated the identification of the geochemical signatures essential for accurate matching of the tephra with their source volcanic centres, as well as inter-and intra-core matching of the sediment records. The integration of these geochemical signatures with radiocarbon ages from bulk organic matter and pollen concentrates extracted from the Onepoto sediment record enhanced the reliability of the new age-depth model. This geochemical tephra dataset underpins the chronological framework of the Onepoto tephrastratigraphy, thereby contributing to a deeper understanding of the timing of volcanic activity on New Zealand extquotesingles North Island and its implications for Late Quaternary paleoenvironmental research in the Southwest Pacific.